The Influence of the Agricultural Development Program in Achieving Sustainable Development Goals in Tanete Rilau District, Barru Regency: Quantitative Analysis with SPSS 26 - Muhammad, Mukmin; Masyitah (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2022 The Visual journal